Security and Watering System Counseling Based on Internet of Things (IoT) in Pondok Hijau Indah Residential Area - Lidyawati, Lita; Jambola, Lucia; Darlis, Arsyad Ramadhan; Kristiana, Lisa; Susana, Ratna (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2020)
Nowadays, security and gardening systems in densely populated residential areas are generally done manually. The security system in housing sometimes places security posts at street corners that are some distance from citizen’s homes thus they cannot be monitored at all times. Whereas other problem of watering system in citizen’s homes, someone has to water the plants one by one that it is not efficient in  energy, time and water availability thus that it can reduce the quality of the plants. Internet of Things (IoT) is a concept and method for remote control, monitoring, and various tasks. IoT is connected to a network that it can be accessed anywhere which can make things easier. IoT can be used to solve various problems. One of them is security issues and gardening activities. By using smart home technology, the security system is carried out by placing CCTV (Closed Circuit Television) which can be accessed by the home owner, anytime and anywhere the home owner is located. On the other hand, gardening is one of the most popular hobbies. In this field, IoT can be used to monitor and regulate various things to support gardening activities. In this community service activity, we are proposed a simple automatic gardening system for watering some plants programmatically in Pondok Hijau Indah residence. The system also allows manual human intervention either locally or remotely via the internet to control CCTV and water pumps. To build this smart Home system we will use the Xiaomi Home application from Google Play. In this application, we can set a program to control CCTV and water the plants every day at a certain time periodically, in this case, we set every 7 hours to watering the plants.